Short-Term Postoperative Cognitive Dysfunction and Inflammatory Response in Patients Undergoing Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy: A Pilot Study - Hui Yu; Rui Dong; Yayuan Lu; Xi Yang; Chang Chen; Zongze Zhang; Mian Peng (Hindawi Limited, 2017)
Objectives. To assess the association between short-term postoperative cognitive dysfuction (POCD) and inflammtory response in patients undergoing cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). Design. A prospective cohort study. Setting. University medical centre. Participants. Fifty-one adult patients who had undergone CRS-HIPEC and twenty control participants. Measurements. The inflammatory marker levels in plasma and cognitive function were measured. Results. Twenty (39.2%, 20/51) patients developed POCD at 1 w after CRS-HIPEC. The patients with POCD had higher serum interleukin 1β (IL-1β), serum amyloid A (SAA), S100 calcium-binding protein β (S-100β), and high mobility group box-1 protein (HMGB-1) levels at 1 and 24 h postoperatively than patients without POCD. There was an association between POCD and the maximum IL-1β and S-100β concentrations in serum, which remained following adjustment for age and FBS. Conclusion. In this pilot study, perioperative inflammatory marker levels increase significantly after CRS-HIPEC in adult patients, and such elevations are associated with the development of short-term cognitive dysfunction after this complex surgery. These results suggested the need for a larger RCT to replicate and confirm these findings.